2010
DOI: 10.1007/s10295-010-0896-1
|View full text |Cite
|
Sign up to set email alerts
|

Engineering industrial Saccharomyces cerevisiae strains for xylose fermentation and comparison for switchgrass conversion

Abstract: Saccharomyces' physiology and fermentation-related properties vary broadly among industrial strains used to ferment glucose. How genetic background affects xylose metabolism in recombinant Saccharomyces strains has not been adequately explored. In this study, six industrial strains of varied genetic background were engineered to ferment xylose by stable integration of the xylose reductase, xylitol dehydrogenase, and xylulokinase genes. Aerobic growth rates on xylose were 0.04-0.17 h(-1). Fermentation of xylose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 33 publications
2
60
0
1
Order By: Relevance
“…Although S. cerevisiae is the most commonly used organism for industrial ethanol production, its inefficient fermentation of pentoses has hampered the production of ethanol from lignocellulosic biomass (21). Recombinant yeast strains expressing transgenes that facilitate integration of xylose into central carbon metabolism have been constructed (22,23). However, when they are grown in mixed glucose/xylose cultures, which would be encountered in lysates of cellulosic biomass, they rapidly ferment all available glucose and then shift into a respiratory metabolic state in which little if any ethanol is produced (23).…”
Section: Significancementioning
confidence: 99%
“…Although S. cerevisiae is the most commonly used organism for industrial ethanol production, its inefficient fermentation of pentoses has hampered the production of ethanol from lignocellulosic biomass (21). Recombinant yeast strains expressing transgenes that facilitate integration of xylose into central carbon metabolism have been constructed (22,23). However, when they are grown in mixed glucose/xylose cultures, which would be encountered in lysates of cellulosic biomass, they rapidly ferment all available glucose and then shift into a respiratory metabolic state in which little if any ethanol is produced (23).…”
Section: Significancementioning
confidence: 99%
“…Yeast strains employed in industrial applications are subject to continuous selection, often resulting in the development of robust stress-tolerant properties (1). Some of these industrial strains that have been metabolically engineered for xylose utilization outperform laboratory strains in the fermentation of pretreated lignocellulosic hydrolysates (19,51,52). In two specific cases, faster xylose fermentation has been independently obtained by engineered industrial strains evolved on defined media containing a cocktail of inhibitors found in dilute acid-pretreated spruce hydrolysate (53) or selected on SO 2 -impregnated steam explosion-pretreated spruce hydrolysate (54).…”
mentioning
confidence: 99%
“…In both cases, eng1 gene expression in yeast, with its native signal sequence for secretion, was under the control of the strong GAP-DH promoter. The HO endonuclease is not expressed in yeast with high ploidy, and is active only in haploid organisms (Hector et al, 2011); deletion of the HO gene does not affect the growth rate and viability of yeast (Baganz et al, 1997;Voth et al, 2001).…”
Section: Discussionmentioning
confidence: 99%